AKRONIM DALAM BAHASA JAWA - NFN Herawati (Kantor Bahasa Kalimantan Timur, 2016)
Language is a means of communication that has developed greatly. Some problems appear in its development such as acronyms in Javanese language. Acronym is an abbreviation consisting of the first letters of each word in the name of something, pronounced as a word. The key issues in this paper are (1) acronym patterns in Javanese language, (2) the most dominant acronym patterns used in Javanese language, and (3) factors that influence the use of acronyms in Javanese language. The object of this paper is acronyms used by native speakers of Javanese language in written and spoken forms. It aims to (1) describe acronym patterns in Javanese language, (2) describe the most dominant acronym patterns used in Javanese language, and (3) describe factors contributing to the acronyms used in Javanese language. It used descriptive-qualitative method, including collecting the data, processing the data, and explaining the result. It revealed 12 acronym patterns in Javanese language. The most dominant one is syllabification pattern on the last syllable in every component. The factors influencing the use of the acronyms are associated with (1) language efficiency (2) euphemism, (3) taboos’ concealment, (4) greetings, (5) satires, and (6) advices.